If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -31 + 5k = 6(8k + 2) Reorder the terms: -31 + 5k = 6(2 + 8k) -31 + 5k = (2 * 6 + 8k * 6) -31 + 5k = (12 + 48k) Solving -31 + 5k = 12 + 48k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-48k' to each side of the equation. -31 + 5k + -48k = 12 + 48k + -48k Combine like terms: 5k + -48k = -43k -31 + -43k = 12 + 48k + -48k Combine like terms: 48k + -48k = 0 -31 + -43k = 12 + 0 -31 + -43k = 12 Add '31' to each side of the equation. -31 + 31 + -43k = 12 + 31 Combine like terms: -31 + 31 = 0 0 + -43k = 12 + 31 -43k = 12 + 31 Combine like terms: 12 + 31 = 43 -43k = 43 Divide each side by '-43'. k = -1 Simplifying k = -1
| 0.5x=0.2x+3 | | x-(-5)=4+x | | 11y-9y+1=17 | | x-(-5x)=4+x | | .5x-41.75=37.25 | | 2Xh/15=20 | | -5m=6 | | 5/8=x/48 | | -48(-5/12=5/16 | | -1*(8n+7)= | | .4a=46 | | a+0.08a=1296 | | 5x^2-8x=8 | | 2*9n=7 | | 3-(2/9b)=(2/3b)-7 | | .75c=11.25 | | (2)2/3e=1/18 | | 4x-12=6x-12-2x | | x+4+x+5+x+2=x+3+x+1+x+3+x+1 | | 25x+16-36x=46+12 | | 1.1p=5.28 | | 8*6x=10*9x | | 2x+4[2-(5x-3)]=0 | | 2(0.5x+x-10)=2(x-6+0.25x) | | y=2.9 | | (-2u^2+5u+3)-(-9u^2-7u+3)= | | x^4+5x-2=0 | | p+(-3p+6)=4a(-5p+3)-10p | | 9=12x-6-7x | | n^2-2n=11 | | x^(2/3)=9 | | Y=sin(16x) |